Improving Disaster Mitigation Capability from an Early Age by Strengthening Disaster Literacy for Students at SD Negeri 10 Bonepantai Bone Bolango Regency - Intan Noviantari Manyoe; Yayu Indriati Arifin; Ahmad Zainuri; Windayani Ika Yunitasari; Naafi Syahna Firdhaus Biya (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
Tihu Village is located on the southern coast of Gorontalo and is included in an area prone to earthquakes and tsunamis. The impact of the earthquake and tsunami disaster can be in the form of loss of life and material. The losses incurred as a result of a disaster are usually caused by the local community's lack of responsiveness in dealing with an impending disaster. Mitigation efforts are needed in tsunami-prone areas to prevent casualties and material losses. Mitigation efforts can be carried out by socializing the earthquake and tsunami disaster and making tsunami evacuation routes. The programs implemented through this service activity are: 1) survey of potential disasters and identification of disaster-prone zones; 2) manufacture of disaster risk reduction information boards; 3) construction of evacuation route boards and assembly points; 4) Socialization of earthquake and tsunami disaster risk reduction; 5) Installation of evacuation route boards and assembly points.